An Advanced Dual‐Function MnO2‐Fabric Air Filter Combining Catalytic Oxidation of Formaldehyde and High‐Efficiency Fine Particulate Matter Removal. (18th August 2020) - Dai, Zijian; Zhu, Jie; Yan, Jiaqi; Su, Jiafei; Gao, Yunfei; Zhang, Xing; Ke, Qinfei; Parsons, Gregory N.
Abstract: Comprehensive treatment of indoor contaminants such as volatile organic compounds (VOCs) and fine particulate matter (PM2.5 ) using transition metal oxide catalysts or functional fibrous filters has gained substantial attention recently. However, coupling VOC oxidation catalysts into high‐performance filter systems remains a challenge. Herein, an overall solution to strongly bind manganese dioxide (MnO2 ) nanocrystals onto polypropylene (PP) nonwoven fabrics is provided. For the first time, uniform heterogeneous nucleation and growth of MnO2 onto PP nonwoven fabrics using intermediate inorganic nucleation films, including Al2 O3, TiO2, and ZnO, formed conformally on the fabrics via atomic layer deposition (ALD) are demonstrated. How different ALD thin films influence the crystallinity, morphology, surface area, and surface oxygen species of the MnO2 grown ALD‐coated PP fibers is further investigated. In addition to uniformity and integrity, ZnO thin films give rise to MnO2 crystals with the largest fraction of available surface oxygen, enabling 99.5% catalytic oxidation of formaldehyde within 60 min. Moreover, the metal oxide filters provide excellent PM removal efficiencies ( e PM), achieving e PM2.5 90% and e PM10 98%, respectively, making the approach an outstanding method to produce fully dual‐functional filtration media. Abstract : A novel dual‐function MnO2 ‐fabric filter is fabricated via uniform heterogeneous nucleation and growth of MnO2 onto polypropylene fabrics with the assistance of atomic layer deposition nucleation layers. The composite filters show ultrafast catalytic oxidation ability of formaldehyde and excellent particulate matter abatement capability, which make them useful for personal protection, indoor air purification, and numerous related applications.